2022
DOI: 10.1016/j.pmn.2021.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Pain and Affected Symptoms of Patients with Rheumatoid Arthritis During COVID-19 Period

Abstract: Background Aim: The aim of this study is to determine the symptoms, pain, and function changes experienced by rheumatoid arthritis patients during the COVID-19 pandemic. Method This descriptive study was completed with a total of 119 patients from the rheumatology clinic of a university hospital who met the follow-up research criteria and agreed to participate in the study. Descriptive features question form, pandemic period disease characteristics form, and Visual Anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 18 publications
(20 reference statements)
0
10
0
Order By: Relevance
“…Two studies reported a COVID-19 infection rate of 2–3% [ 29 , 30 ]. One study excluded patients with COVID-19 infection [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two studies reported a COVID-19 infection rate of 2–3% [ 29 , 30 ]. One study excluded patients with COVID-19 infection [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Increased disease activity, functional impairment, and pandemic-related psychological stress all correlated to significant decreases in quality of life among RA patients [ 29 , 32 ]. Of the four studies, three discussed patients’ inability to access healthcare resources despite having a clear need, with 53% of patients lacking the support of a healthcare professional [ 31 ], and 59–87% of patients reporting difficulty obtaining medications [ 29 , 30 ]. Decreased healthcare access was associated with increased symptom severity in two studies [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations